Local and regional flaps in head & neck reconstruction : a practical approach - Fernandes, Rui (Ames, Iowa : Wiley-Blackwell, 2014)
Local and Regional Flaps in Head & Neck Reconstruction: A Practical Approach provides comprehensive, step-by-step instruction for flap raising and insetting for the head and neck region. Ideal for oral and maxillofacial surgeons, facial plastic surgeons, and head and neck surgeons, the book serves as a useful guide to planning reconstructive cases and an easily accessible reference prior to operation.Local and Regional Flaps in Head & Neck Reconstruction is logically organized into 24 chapters, each focusing on a local or regional flap, or a special site reconstruction. Chapters focused on a.
Flap classification -- Bilobed flap -- Rhomboid flap -- Crescentic flap -- Septal flap -- Nasolabial flap -- V to Y advancement flap -- Keystone flap -- Paramedian forehead flap -- The temporoparietal fascia flap -- Temporalis muscle flap -- Cervicofacial advancement flap -- Submental island flap -- Pectoralis major myocutaneous flap -- Latissimus dorsi myocutaneous flap -- Sternocleidomastoid flap -- Trapezius flap -- The supraclavicular artery island flap -- The internal mammary perforator flap -- Ear reconstruction -- Lip reconstruction -- Nasal reconstruction -- Scalp reconstruction.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Head -- surgery; Neck -- surgery; Reconstructive Surgical Procedures; Surgical flaps; Head -- Surgery; Neck -- Surgery; Flaps (Surgery); MEDICAL / Surgery / General; Flaps (Surgery); Head -- Surgery; Neck -- Surgery; Electronic books; Electronic books; Electronic books